In vivo responses of cutaneous C-mechanosensitive neurons in mouse to punctate chemical stimuli that elicit itch and nociceptive sensations in humans - Ma, C. (American Physiological Society, 2012)
Native cowhage spicules, and heat-inactivated spicules containing histamine or capsaicin, evoke similar sensations of itch and nociceptive sensations in humans. In ongoing studies of the peripheral neural mechanisms of chemical itch and pain in the mouse, extracellular electrophysiological recordings were obtained, in vivo, from the cell bodies of mechanosensitive nociceptive neurons in response to spicule stimuli delivered to their cutaneous receptive fields (RFs) on the distal hindlimb. A total of 43 mechanosensitive, cutaneous, nociceptive neurons with axonal conduction velocities in the C-fiber range (C-nociceptors) were classified as CM if responsive to noxious mechanical stimuli, such as pinch, or CMH if responsive to noxious mechanical and heat stimuli (51°C, 5 s). The tips of native cowhage spicules, or heat-inactivated spicules containing histamine or capsaicin, were applied to the RF. Heat-inactivated spicules containing no chemical produced only a transient response occurring during insertion. Of the 43 mechanosensitive nociceptors recorded, 20 of the 25 CMHs responded to capsaicin, and of these, 13 also responded to cowhage and/or histamine. In contrast, none of the 18 CMs responded to any of the chemical stimuli. The time course of the mean discharge rate of CMHs was similar in response to each type of spicule and generally similar, although reaching a peak earlier, to the temporal profiles of itch and nociceptive sensations evoked by the same stimuli in humans. These findings are consistent with the hypothesis that the itch and nociceptive sensations evoked by these punctuate chemical stimuli are mediated at least in part by the activity of mechanoheat-sensitive C-nociceptors. In contrast, activity in mechanosensitive C-nociceptors that do not respond to heat or to pruritic chemicals is hypothesized as contributing to pain but not to itch.